Deactivation Mechanism of Potassium on the V2O5/CeO2 Catalysts for SCR Reaction: Acidity, Reducibility and Adsorbed-NOx - Peng, Yue; Li, Junhua; Huang, Xu; Li, Xiang; Su, Wenkang; Sun, Xiaoxu; Wang, Dezhi; Hao, Jiming (Environmental science & technology, 2014)
A series of V2O5/CeO2 catalysts with different potassium loadings were prepared to investigate alkali deactivations for selective catalytic reduction of NOx with NH3. An alkali poisoning mechanism could be attributed to surface acidity, reducibility, and NOx adsorption/desorption behaviors. The detailed factors are as follows: (1) decrease of surface acidity suppresses NH3 adsorption by strong bonding of alkali to vanadia (major factor); (2) low reducibility prohibits NH3 activation and NO oxidation by formation bonding of alkali to vanadia and ceria (important factor); (3) active NOx(-) species at low temperature diminish because of coverage of alkali on the surfaces (minor factor); and (4) stable, inactive nitrate species at high temperature increase by generating new basic sites (important factor).